Occurrence of Carpal Tunnel Syndrome in Chronic Hemodialysis Patients - Intissar Haddiya; Hicham Yacoubi; Fatima Zahra Berkchi (Medical Science: Trends and Innovations Vol. 7, 2025)
Background: Despite significant advances in hemodialysis (HD) practice, carpal tunnel syndrome (CTS) remains a clinical concern among patients. Carpal tunnel syndrome (CTS) is a well-known manifestation of dialysis-related amyloidosis, mainly caused by the deposition of \(β\)2- microglobulin in the carpal tunnel. It is considered the most common mononeuropathy in endstage renal disease (ESRD) patients. Aim: This study aimed to evaluate the prevalence of CTS and identify factors associated with its occurrence in chronic HD patients. Methods: A cross-sectional study was conducted in December 2017, including consenting chronic HD patients with a dialysis vintage of at least three months, at a reference state center in Oujda, Eastern Morocco. CTS diagnosis was based on reported symptoms, clinical signs, and positive Tinel and Phalen manoeuvres. Symptomatic patients underwent electromyography (EMG) on non-dialysis days, performed by the same neurologist under standardized conditions. Data were analyzed using SPSS version 20.0 for Windows. Chi-square or Fisher exact tests were used for analyzing the correlation among categorical variables. Results: A total of 112 chronic HD patients meeting the inclusion criteria were enrolled. CTS was diagnosed and confirmed by nerve conduction studies in 8.04% of patients. Diabetic nephropathy was the most common underlying nephropathy, observed in 36.3% of CTS cases. Patients with CTS were older (mean age: 52.99 ± 11.32 vs. 48.4 ± 12.6; p=0.002), predominantly male (63.6% vs. 55.4%; p=0.03), and active smokers in 18.5% of cases. CTS patients also had a longer HD duration (95.8 ± 15.75 vs. 82.11 ± 17.22 months; P<0.001). Additionally, CTS was significantly associated with a higher prevalence of diabetes mellitus (36.3% vs. 13.8%; p<0.001), hepatitis C virus (HCV) infection (18.18% vs. 2.97%; p=0.02), and reduced urine output (<100 ml/day: 27.2% vs. 3.98%; P=0.003). Multivariate logistic regression analysis revealed that HCV infection (OR: 1.45, 95% CI: 1.17–1.87, p=0.034), prolonged HD vintage (OR: 1.95, 95% CI: 1.89–3.65, P<0.001), and urine output <100 ml/day (OR: 1.72, 95% CI: 1.03–2.57, P=0.01) were independently associated with CTS. Conclusion: This cross-sectional study highlights that prolonged dialysis vintage, HCV infection, and loss of residual renal function are key factors associated with CTS in chronic HD patients. The surgical release procedure of the wrist is an effective treatment method. Further research is needed to elucidate the underlying mechanisms and pathogenesis of CTS in this patient population.